(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
In recent years, participation and interactivity have become two key words in the vocabulary of art criticism. It is not by chance that both these models insist on a form of performative spectatorship, based essentially on three concepts: presentness, immediateness and unframedness. The challenge posed by this type of spectatorship concerns a fundamental concept for aesthetics (already with Kant’s Critique of the Power of Judgment), and that is that of spontaneity. In fact, the creation of an “unframed” space and an immediate experience precisely at increasing the “spontaneity effect,” fuelled by the active involvement of a spectator “immersed” physically (and emotionally) within an environment/work that is programmed to welcome and receive its intervention. Except that spontaneity is, by definition, something that cannot be achieved if sought intentionally. This is precisely the challenge posed by interactivity.